Private Homecare Practices by Healthcare Professionals: A Comparative Civil Law Analysis between Indonesia and Saudi Arabia - Sukmawan, Yulia Audina; Sari, septiana; Fahlani, Soffyan Angga; Mursalin, Arisandy; Noor, Layla Abdullah (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Private homecare is part of the development of healthcare services that allows medical personnel to be present directly in the patient's home. In Indonesia, private homecare poses problems because there are no specific regulations in place.Purposes of the Research: To analyze private homecare practices in private homes from a civil law perspective, comparing Indonesia and Saudi Arabia.Methods of the Research: This research is a mixed-methods legal study, combining normative and empirical legal research.Results Main Findings of the Research: This study confirms that private homecare in Indonesia has significantly developed as an independent healthcare service provided by professional medical personnel for patients. A comparison of civil law with Saudi Arabia shows that Indonesia relies on the Civil Code Articles 1233-1253, 1320, 1365, which allows oral contracts to be prone to breach (Articles 1234, 1266) without SNI medical records or mandatory insurance. In contrast, Saudi Arabia implements the Civil Transactions Law RD M/191/1444H Articles 128-137 with mandatory written ijara contracts (Labor Law RD M/51/1426H), CBAHI accreditation 2024, the Sehhaty digital platform, and professional insurance (Health Insurance Law RD M/32/1424H Article 17). The research recommends that Indonesia adopt national contract standards, a special homecare SIP, strict supervision by the Health Department/PPNI, and an integrated SATUSEHAT platform like the Saudi model to create an accountable ecosystem that balances the flexibility of nursing practice with civil law certainty for chronic patients, in order to realize the right to health as a human right